Mechanism of Mongolian Medicine Batri-7 on Salmonella Enteritis - Yang D; Chen S; Borijihan H; Aoqier A; Sarula S; Siqin S; Manda M; Temuqile T; Baigude H (Journal of Inflammation Research)
Dezhi Yang,1,* Shana Chen,1,* Haiyan Borijihan,1 Aoqier Aoqier,1 Sarula Sarula,1 Siqin Siqin,1 Manda Manda,1 Temuqile Temuqile,1 Huricha Baigude1,2 1National and Local Joint Engineering Research Center of Modern Mongolian Medicine Research and Testing, International Mongolian Hospital of Inner Mongolia, Hohhot, 010065, People’s Republic of China; 2School of Chemistry & Chemical Engineering, Inner Mongolia University, Hohhot, Inner Mongolia, 010020, People’s Republic of China*These authors contributed equally to this workCorrespondence: Temuqile Temuqile, International Mongolian Hospital of Inner Mongolia, Hohhot, Inner Mongolia, 010065, People’s Republic of China, Tel +86 139-4711-9993, Email tmqyx01@163.com Huricha Baigude, Institute of Mongolian Medicinal Chemistry, School of Chemistry & Chemical Engineering, Inner Mongolia University, Hohhot, 010020, People’s Republic of China, Email hbaigude@imu.edu.cnPurpose: Traditional Mongolian Medicine Batri-7 (BT-7) is the key Mongolian Medicine (MM) for bacterial enteritis. BT-7 is a well-known clinical MM due to its antibacterial properties. BT-7 contains plant-derived bioactive compounds, but its molecular mechanism of action remains unclear. This study explores BT-7’s antibacterial compounds and therapeutic mechanism in a Salmonella enteritis mouse model.Methods: The active components of BT-7 were detected by liquid chromatography-tandem mass spectrometry assay and identified by UPLC/Q-TOF-MS. An enteritis mouse model induced by Salmonella typhimurium was used in this study. Pathological analysis of small intestine was conducted with hematoxylin and eosin staining. The macrophage recruitment in model mice’s intestines was detected by flow cytometry. Simultaneously, the Minimum Inhibitory Concentration of BT-7 was evaluated against bacterial by microbroth dilution method, BT-7 regulation of Salmonella typhimurium gene was performed by RNA-Seq methods and verified by qRT-PCR.Results: In the LC-MS/MS assay, negative and positive-ion modes are identified for 511 and 699 compounds from BT-7, respectively. Of them, we found multiple antibacterial and anti inflammation compounds including chrysin, oroxylin A and luteolin. In vivo, we observed that treatment of mouse Salmonella enteritis with BT-7 decreases inflammation score and macrophages on intestinal tenue. In vitro, BT-7 presented the highest antibacterial activities against tested strains with MIC was 2– 4 mg/mL. Meanwhile, BT-7 significantly down regulated Salmonella infection genes.Conclusion: Twenty key anti-bacterial components were identified in the BT-7. In vivo experiment shows that orally administered BT-7 effectively reduce the inflammation of intestine in model of Salmonella-induced mouse enteritis by down regulating the infection-related virulence genes of Salmonella. Through this study, we discovered the mechanism of BT-7’s dual action on the host and pathogenic bacteria. This gives inspiration for anti-infective disease research in traditional medicine and also proves that traditional medicines still have good prospects for treating infectious diseases.Keywords: Mongolian medicine, Batri-7, antibacterial, Salmonella enteritis, virulence gene